The exciting way of speaking of chilean people: generalities (Contextos: Estudios de Humanidades y Ciencias Sociales, 2018)
It is frequent in intellectual circles to hear that Chilean people have a careless way of speaking and, therefore, that it is difficult to understand. There are shortened words, many idioms, neologisms, indigenisms, nicknames, a lot of body language to communicate and also a pinch of humor in the language, especially orally. But the Spanish used by Chilean people is the linguistic expression of a part of America. Technically, the Spanish of Chile is a variant of Spanish. Along with looking into the causes of Chileans’ way of speaking, we have to explore the history of Chile. In that exercise, we will find that most of the conquerors who brought along Castilian were not exactly scholars or great wise men of the language.In this work, the general principles of the lexicon and in part, of the pronunciation of the Spanish of Chile and its implication for the culture of Chile will be discussed.